Designing and Developing Four Games for Rehabilitation of the Wrist Complex and Forearm Complex: An Action Research - Zahra Moradi-Shahrbabak; Zahra Nasr-Esfahani; Hamed Garousi; Zahrasadat Rezaeian (Vesnu Publications, 2020)
Introduction: Virtual reality (VR) games are among the rehabilitation strategies that, while effective, are attractive to the individual and facilitate and encourage proper movement. In this study, four VR games were designed and assessed to encourage the movements of the forearm and wrist complexs. Materials and Methods: The games were designed using the leap motion device, a small non-tactile device with good spatial resolution. Cameras were responsible for detecting the depth and distance of the hand from the device, and the infrared sensors were responsible for detecting hand movements. In order to determine the level of attractiveness of the game for people with upper motor neuron disorders, three individuals aged 18 to 41 were randomly selected from among the people referred to the physiotherapy department of Al-Zahra Educational and Medical Center, Tehran, Iran. Results: The effectiveness of the games was confirmed by board members of department of physical therapy. Three games were applicable in the early stages of rehabilitation for all three participants. One game could not be used in the early stages of rehabilitation due to the complexity of the required movement. Conclusion: The four designed games required the basic movements required for daily and self-care activities and seemed to appeal the younger users.